Assessment of Immunization Coverage of Pediatric Population in Telangana - Girish Manohar Chavan; Mavatkar MV (National Journal of Community Medicine, 2019)
Background: The immunization coverage in India is far away from acceptable level with complete immunization coverage being only 62% at the national level. Targeting efforts towards poor per- forming areas and knowing the determinants of non- immunization and dropouts offers a quick solution.